The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/cells11233849
|View full text |Cite
|
Sign up to set email alerts
|

The Biological Effects of Compound Microwave Exposure with 2.8 GHz and 9.3 GHz on Immune System: Transcriptomic and Proteomic Analysis

Abstract: It is well-known that microwaves produce both thermal and nonthermal effects. Microwave ablation can produce thermal effects to activate the body’s immune system and has been widely used in cancer therapy. However, the nonthermal effects of microwaves on the immune system are still largely unexplored. In the present study, we exposed rats to multifrequency microwaves of 2.8 GHz and 9.3 GHz with an average power density of 10 mW/cm2, which are widely used in our daily life, to investigate the biological effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…Cytokines are critical effectors in regulating both anti-virus and anti-tumor immune responses via direct cytotoxicity and indirectly activating immune cells, such as B lymphocytes and natural killers [ 50 , 51 ]. We previously reported that multifrequency microwaves of 2.8 GHz and 9.3 GHz significantly increased the expression of IL-1α, IL-1β, and IL-4 at 6 h after exposure, which, in turn, up-regulated B lymphocytes at 7 d after exposure in peripheral blood [ 52 ]. However, no obvious changes of IL-1α, IL-1β, and IL-4 were observed at 6 h after exposure to the multifrequency microwave of 1.5 GHz and 2.8 GHz in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines are critical effectors in regulating both anti-virus and anti-tumor immune responses via direct cytotoxicity and indirectly activating immune cells, such as B lymphocytes and natural killers [ 50 , 51 ]. We previously reported that multifrequency microwaves of 2.8 GHz and 9.3 GHz significantly increased the expression of IL-1α, IL-1β, and IL-4 at 6 h after exposure, which, in turn, up-regulated B lymphocytes at 7 d after exposure in peripheral blood [ 52 ]. However, no obvious changes of IL-1α, IL-1β, and IL-4 were observed at 6 h after exposure to the multifrequency microwave of 1.5 GHz and 2.8 GHz in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Short-term exposure to highintensity microwave radiation has been linked to symptoms such as heart palpitations, sleep disturbances and sinus arrhythmias in both national and international studies [2,3]. In addition, prolonged exposure to high-intensity microwave radiation can lead to changes in the blood and lymphatic systems, which may affect the function of the immune system [4,5]. These findings highlight the importance of further research and regulation to mitigate potential health risks associated with microwave technology.…”
Section: Introductionmentioning
confidence: 99%